Sistem Informasi Pemesanan Bus Pariwisata Berbasis Web pada “Dikma Transport” - Emienda Qunurul Bahri Mahardika Mahardika (JURNAL PILAR TEKNOLOGI Jurnal Ilmiah Ilmu Ilmu Teknik, 2023)
Dikma Transport Company is a service company engaged in transportation. In the process of ordering transactions still using the manual method, so the data has not been computerized. This causes the slow search of customer data in the rental process and preparing bus booking reports. In addition, customers must also come to the location directly to place an order or obtain the required information. The purpose of making this information system is to make it easier for company owners to manage transaction data and make reports, so that the data can be computerized properly. In addition, the existence of this information system is expected to increase customer satisfaction. This information system is made using the codeigniter framework and the development method is the waterfall with the stages of literature study, observation data collection, and software development. The result of this research is the creation of a tourism bus ordering information system on a web-based "Dikma Transport" that can provide convenience to company owners to manage transaction data and report generation. In addition, the data processing process which was previously still manual using paper media, is now computerized so as to increase efficiency and effectiveness.